Migration and displacement of people with disabilities in Iraq (Historical study) (Journal of Misan Researches, 2025)
Disability was and still is one of the social phenomena that has attracted the attention of many philosophers, thinkers, and even clerics and politicians, past and present, which has made it a global phenomenon about which opinions have differed across the ages and cultures in terms of its concept and ways of treating it. If we consider the issue of the disabled as a global issue, then attention is supposed to be paid to the issue of the disabled in terms of His psychological and physical conditions and his social and economic conditions Because interest in caring for the disabled represents an essential factor through which a positive change can be brought about in the social and economic structure of society, and refusing the disabled person to enter the field of work as sick or disabled is considered blatant racial discrimination that is rejected by all divine and human legislation and laws, because all barriers and laws that It prevents the integration of this group of society into various social, economic and cultural activities And not to marginalize it and consider it useless, and accordingly, the concept of disability is highlighted and the causes and effects behind the migration and displacement of people with disabilities in Iraq are explained, and in conclusion, a set of recommendations are proposed to reduce this phenomenon and its dangerous repercussions on the individual and society together.